2021
DOI: 10.23869/bphjbr.27.2.20222
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antibiofilm effect of silver and gold nanoparticles in Uropathogenic Escherichia coli

Abstract: Nosocomial infections of the urinary tract are the most common nosocomial infections. Infectious diseases currently pose a life threatening due to the increasing phenomenon of infectious agent resistance. One of the factors known to cause resistance to broad-spectrum antimicrobials agent is the susceptibility to biofilm formation. The use of silver nanoparticles (NPs) is now regarded as one of the most promising strategies to target infections associated with biofilms. This study aims to determine the applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The antimicrobial potentials of GANP were dependent upon the perturbations that occurred in different bacterial components and the biofilm. All biofilm penetration methods involved hydrophobic interaction, hydrogen bonding, electrostatic, and van der Waals attraction-based interactions 61 , 62 . The current results were in agreement with previous result 63 wherein it was exhibited that the AuNPs capping by Arabic Gum exhibited a noteworthy anti-adhesion activity against Cutibacterim acne.…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial potentials of GANP were dependent upon the perturbations that occurred in different bacterial components and the biofilm. All biofilm penetration methods involved hydrophobic interaction, hydrogen bonding, electrostatic, and van der Waals attraction-based interactions 61 , 62 . The current results were in agreement with previous result 63 wherein it was exhibited that the AuNPs capping by Arabic Gum exhibited a noteworthy anti-adhesion activity against Cutibacterim acne.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, through electrostatic interactions, AuNPs cause mechanical damage to cell membranes. Furthermore, the release of metal ions from AuNPs can induce ROS generation and damage cell structure, function, and proteins . In addition to adhesion, another fundamental process is quorum sensing (QS).…”
Section: The Mechanism Of Mnps In Antimicrobial Activitiesmentioning
confidence: 99%
“…Furthermore, the release of metal ions from AuNPs can induce ROS generation and damage cell structure, function, and proteins. 100 In addition to adhesion, another fundamental process is quorum sensing (QS). Several studies have shown that metal NPs can disrupt the production of QS molecules, especially self-inducers (AI-2).…”
Section: Ion Releasementioning
confidence: 99%
“…A 5 mL culture was prepared in a 24-well microplate for the specified treatment, comprising 3 mL of liquid RPMI media, a glass coverslip enveloped with biofilm, 1 mL of gold nanoparticle solution (E), and 1 mL of silver nanoparticle solution (P) at concentrations of 25, 50, 75, and 100 ppm. The chosen concentrations were based on findings from prior research by Purbowati et al (2022), highlighting varied antibiofilm activity via the crystal violet method. This culture was incubated at 37 ºC for 24 h under aerobic conditions.…”
Section: The Addition Of Gold Nanoparticles and Silver Nanoparticlesmentioning
confidence: 99%